Self-compacting concrete incorporating electric arc-furnace steelmaking slag as aggregate. (5th February 2017) - Santamaría, A.; Orbe, A.; Losañez, M.M.; Skaf, M.; Ortega-Lopez, V.; González, Javier J.
Abstract: Electric arc-furnace slag (EAFS) is an industrial by-product that can be employed in hydraulic mixes used in the field of construction and civil engineering. The design and preparation of self-compacting mixes with this aggregate is a challenge, due to the loss of workability that always accompanies its use in concrete. Only through careful design of the characteristics and proportions of the components in each mixture will an acceptable workability be achieved. Thus, criteria and methods are proposed in this paper for successful preparation of these types of mixtures. Several concrete mixes are manufactured to obtain self-compaction characteristics and their main properties are analyzed with regard to their use as structural concrete. Electron microscopy observations and dispersive energy analysis are used to study the microstructural features of these mixes. Finally, a numerical simulation is proposed as a useful method that estimates the viscous properties of the mixes and their workability, based on the dosage and the characteristics of their components. Highlights: SCC mixes using EAF slag as aggregate have been successfully manufactured Criteria and methods are developed for successful preparation of these types of mixtures SCC mixes showed promising results in terms of their mechanical properties for structural applications The proposed numeric model can captured the rheological behavior of the mixture Graphical abstract: